2017
DOI: 10.1002/bdra.23563
|View full text |Cite
|
Sign up to set email alerts
|

Association between a Maternal History of Miscarriages and Birth Defects

Abstract: Results: Control mothers with vs. without previous miscarriages were older, had had more pregnancies, and were less educated. Three risk models for miscarriages were observed: highest risk for gastroschisis, omphalocele, and talipes; only one miscarriage for spina bifida, and only two or more for hypospadias.Conclusion: Based on these three models, the following common factors for each BD/miscarriage association are proposed: infertility therapies for hypospadias, vascular disruption for gastroschisis and tali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Previously, no clear risk factors for PBS have been reported. History of recurrent miscarriages has been reported to increase the risk of omphalocele, and also of other congenital anomalies [14,17,18]. Although our results suggest that recurrent miscarriages would be a risk factor for PBS, further studies are warranted to confirm this finding.…”
Section: Discussionmentioning
confidence: 45%
“…Previously, no clear risk factors for PBS have been reported. History of recurrent miscarriages has been reported to increase the risk of omphalocele, and also of other congenital anomalies [14,17,18]. Although our results suggest that recurrent miscarriages would be a risk factor for PBS, further studies are warranted to confirm this finding.…”
Section: Discussionmentioning
confidence: 45%
“…A high parity implies that more internal and external environmental factors exist in the mother, which may be related to the high proportion of chromosomal abnormalities in the women. Regarding miscarriage, it has been confirmed that miscarriage history is associated with gastroschisis, omphalocele, talipes, spina bifida, and hypospadias [ 24 ]. Birth cohort studies revealed that autoimmune diseases can influence time-to-pregnancy, pregnancy loss, and live birth rate [ 25 ]; miscarriage history is associated with bacterial vaginosis (eg, septic abortion [ 26 ]), which can induce huge toxicity to the fetus [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the prevalence of infantile male hypospadias may be underestimated since 20% of the sample was lost to follow-up and possibly included women with miscarriages and terminated pregnancies. Fetuses born from these women were considered to have a high prevalence of birth defects [ 44 , 45 ]. However, the association between APP and male hypospadias should not be affected by the underestimation.…”
Section: Discussionmentioning
confidence: 99%